Expanding horizons: new roles for non-canonical RNA-binding proteins in cancer. (February 2018) - Moore, Samantha; Järvelin, Aino I; Davis, Ilan; Bond, Gareth L; Castello, Alfredo
Abstract : Cancer development involves the stepwise accumulation of genetic lesions that overcome the normal regulatory pathways that prevent unconstrained cell division and tissue growth. Identification of the genetic changes that cause cancer has long been the subject of intensive study, leading to the identification of several RNA-binding proteins (RBPs) linked to cancer. Cross-reference of the complement of RBPs recently identified by RNA interactome capture with cancer-associated genes and biological processes led to the identification of a set of 411 proteins with potential implications in cancer biology. These involve a broad spectrum of cellular processes including response to stress, metabolism and cell adhesion. Future studies should aim to understand these proteins and their connection to cancer from an RNA-centred perspective, holding the promise of new mechanistic understanding of cancer formation and novel approaches to diagnosis and treatment.